Kontext Kunst : The art of the '90s - Avgikos, Jan; Blase, Christoph; Buchloh, Benjamin H.D.; Decter, Joshua; Draxler, Helmut; Dreher, Thomas; Fraser, Andrea; Goldstein, Ann; Groys, Boris; Lyotard, Jean-François; McAllister, Jackie; Meinhardt, Johannes; et al. (Graz Köln : Dumont Buchverlag Köln Neue Galerie am Landesmuseum Joanneum Graz, 1994)
Armaly, Fareed ; Bonin, Cosima von ; Burr, Tom ; Clegg & Guttmann ; Cranston, Meg ; Dion, Mark ; Fend, Peter ; Fraser, Andrea ; Green, Renée ; Jones, Ronald ; Lawler, Louise ; Locher, Thomas ; Malevich, Kasimir ; Maltzahn, Katrin von ; Schwarz, Oliver ; Margreiter, Dorit ; Poledna, Mathias ; Pumhösl, Florian ; Küng, Hans ; Inspection "Medical Hermeneutics" ; Möller, Regina ; Mucha, Reinhard ; Müller, Christian Philipp ; Olschwang, Anton ; Tschernyschowa, Olga ; Perlman, Hirsch ; Peterman, Dan ; Piper, Adrian ; Prina, Stephen ; Rockenschaub, Gerwald ; Scher, Julia ; Simon, Jason ; Stingel, Rudolf ; Tobier, Lincoln ; Williams, Christopher ; Zimmermann, Peter ; Zobernig, Heimo
biog. auteurs p. 610-611
biog. kunstenaars p.572-608
Duits
boek
Keywords: jaren 90